Observation of internal transport barrier in ELMy H-mode plasmas on the EAST tokamak. (6th June 2017) - Yang, Y; Gao, X; Liu, H Q; Li, G Q; Zhang, T; Zeng, L; Liu, Y K; Wu, M Q; Kong, D F; Ming, T F; Han, X; Wang, Y M; et al.
Abstract: The internal transport barrier (ITB) has been obtained in ELMy H-mode plasmas by neutron beam injection and lower hybrid wave heating on the Experimental Advanced Superconducting Tokamak (EAST). The ITB structure has been observed in profiles of ion temperature, electron temperature, and electron density within ρ  < 0.5. It was also observed that the ITB formation is stepwise. Due to the ITB formation, the confinement quality H 98 y 2 increases from 1 to 1.1 and the normalized beta, β N, increases from 1.5 to near 2. The fishbone activity observed during the ITB phase suggests the central safety factor q (0) ∼ 1. Transport coefficients are calculated by particle balance and power balance analysis, showing an obvious reduction after the ITB formation.